A church historical enquiry regarding growth of membership in the church of Central Africa, Presbyterian - Harare Synod (1912 – 2012) - Gunde, Samuel (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.